1973
DOI: 10.1002/eji.1830030811
|View full text |Cite
|
Sign up to set email alerts
|

Normal development of the thymus‐dependent limb of humoral immune responses in mice

Abstract: The capacity o f mice to produce antibody-forming cells (AFC) to sheep erythrocytes and t o low doses of two haptenated proteins increases logarithmically with age in the postnatal period. This increase is prevented by thymectomy. These findings, together with those on the ability o f suckling mice to make high numbers of AFC t o high doses of at least one of the antigens used, indicate that T cells are the limiting cell type in neonatal humoral immune responses. An analysis of variance of the number of AFC in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1975
1975
1977
1977

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The pioneering work of Silverstein et al (37) demonstrated a sequential hierarchy of antibody responsiveness to a variety of antigens in the fetal sheep. However, the interpretation of these experiments was complicated by the fact that the animals were genetically diverse and that other cell types involved in antibody production (T cells and macrophages) are functionally immature at birth (38)(39)(40)(41)(42). Nevertheless, Sherwin and Rowiands (43) still observed a sequential hierarchy of antibody responsiveness when neonatal B cells were provided with mature T cells and macrophages (43).…”
Section: Discussionmentioning
confidence: 99%
“…The pioneering work of Silverstein et al (37) demonstrated a sequential hierarchy of antibody responsiveness to a variety of antigens in the fetal sheep. However, the interpretation of these experiments was complicated by the fact that the animals were genetically diverse and that other cell types involved in antibody production (T cells and macrophages) are functionally immature at birth (38)(39)(40)(41)(42). Nevertheless, Sherwin and Rowiands (43) still observed a sequential hierarchy of antibody responsiveness when neonatal B cells were provided with mature T cells and macrophages (43).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore studied the early Ig production in congenitally thymusless Cnude") mice and their response to lipid A and thymus grafts. The experiments to be presented were also prompted by reports showing that the limiting factor governing the capacity of young mice to give a humoral immune response could be the presence or maturity of thymus-dependent ~'helper" cells (5,6).A number of studies in vitro are concerned with the question whether or not T cells are participants in the stimulation of B cells by LPS or lipid A (7-9). The interpretation of the results is complicated by the finding that the nude mouse does possess some 0-positive cells (10), and that, in fact, LPS itself can induce precursor cells to express T-cell-specific antigens (11).…”
mentioning
confidence: 99%
“…We therefore studied the early Ig production in congenitally thymusless Cnude") mice and their response to lipid A and thymus grafts. The experiments to be presented were also prompted by reports showing that the limiting factor governing the capacity of young mice to give a humoral immune response could be the presence or maturity of thymus-dependent ~'helper" cells (5,6).…”
mentioning
confidence: 99%